Second thoughts on development accounting - Erich Gundlach; Desmond Rudman; Ludger Wößmann (Kiel Institute of World Economics (IfW), 1998)
We estimate the relative roles of factor inputs and productivity in explaining the level of economic development, which is measured as output per worker. For a large sample of countries, we show that alternative identifying productivity assumptions and alternative measures of human capital have a large impact on the relative weights of factor inputs and productivity in a decomposition of output per worker. For a sample of OECD countries, we find that productivity has almost no role in explaining cross-country differences in output per worker. This result supports the reasoning of a traditional neoclassical growth model.
Keywords: O4; 330; Arbeitsproduktivität; Entwicklungskonvergenz; Schätzung; Wachstumstheorie; Humankapital; Technischer Fortschritt; Vergleich; Welt; OECD-Staaten